2015
DOI: 10.1039/c5ra02643a
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted optimization of the manganese redox states for enhanced capacity and capacity retention of LiAlxMn2−xO4 (x = 0 and 0.3) spinel materials

Abstract: Microwave irradiation at the pre-and post-annealing steps of the synthesis of LiAl x Mn 2Àx O 4 (x ¼ 0 and 0.3) spinel cathode materials for rechargeable lithium ion batteries is a useful strategy to optimize the average manganese valence number (n Mn ) for enhanced capacity and capacity retention. The strategy impacts on the lattice parameter, average manganese valence, particle size and morphology, reversibility of the deintercalation/intercalation processes, and capacity retention upon continuous cycling. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
(68 reference statements)
1
16
0
Order By: Relevance
“…Using the SEM images, the estimated particle size range for the compositions x = 0, x = 0.125, x = 0.25, x = 0.375, and x = 0.5, respectively, is 475 nm-2.2 lm, 200-525 nm, 200-800 nm, 300-800 nm, and 200-700 nm. The aluminium-doped samples are small in size compared with pristine LiMn 2 O 4 , in agreement with the literature report [14]. the Li movement by occupying the Li site resulting in unacceptable low capacity.…”
Section: Electrochemical Characterizationsupporting
confidence: 86%
See 2 more Smart Citations
“…Using the SEM images, the estimated particle size range for the compositions x = 0, x = 0.125, x = 0.25, x = 0.375, and x = 0.5, respectively, is 475 nm-2.2 lm, 200-525 nm, 200-800 nm, 300-800 nm, and 200-700 nm. The aluminium-doped samples are small in size compared with pristine LiMn 2 O 4 , in agreement with the literature report [14]. the Li movement by occupying the Li site resulting in unacceptable low capacity.…”
Section: Electrochemical Characterizationsupporting
confidence: 86%
“…Some of the causes for the capacity fade of spinel cathode materials when used as battery materials include two-phase unstable reaction [5], dissolution of spinel into the electrolyte, and decomposition of the electrolyte in the 4 V region [6] and Jahn-Teller distortion in the 3 V region [7]. One of the strategies to retain capacity is by substitution of small amount of Mn ions by dopant ions such as Al, Ni [3,[7][8][9], and microwave irradiation [14]. It is believed that the dopant ions occupy the octahedral 16d sites of Mn ions in the spinel lattice and stabilize the spinel structure from lattice distortion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result confirms microwave treatment reduces the particle size of the powders which is in consistence with previously reported results. 11,25 The HR-TEM images in Figs. 3e and 3f confirm both the samples are crystalline powders.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has shown that microwave irradiation has the ability to improve the morphology and tune the concentration of the Mn 3+ that causes Jahn-Teller distortion and capacity fade in manganese oxide-based lithium-ion batteries. [30][31][32] Fluorination, on the other hand, has been found to improve the stability of electrode materials. [33][34][35][36] This work interrogates and clearly confirms the synergistic effect of the redox property-enhancing features of microwave irradiation and fluorination toward P2-type NaMgMnO material.…”
Section: 23mentioning
confidence: 99%